A numerical simulation of diffusion-convection problems in heterogeneous media with a point source - Solekhudin, Imam; Megawati, Noorma Yulia; Solikhatun,; Anggriani, Indira; Azis, Mohammad Ivan; Magdalena, Ikha; Widowati, (Penerbit Universiti Kebangsaan Malaysia, 2025)
In this paper, some time-independent diffusion-convection problems in anisotropic media are considered. To study the problems, the governing equation of the problems is transformed into a diffusion-convection equation in a homogeneous isotropic media. The transformed equation with respect to transformed boundary conditions are solved numerically using Dual Reciprocity Boundary Element Method (DRBEM). The method is tested using several problems involving time independent diffusion-convection. Two of the problems are with analytical solution, and the other problems are with point sources without known analytical solution.